Asian diplomacy : the foreign ministries of China, India, Japan, Singapore and Thailand - Rana, Kishan S.; DiploFoundation (New Delhi ; Oxford University Press, 2007)
Rana's pioneering comparative examination provides a sound basis for understanding this new diplomatic environment.
CONTENTS: Introduction -- China: Reform and Refinement -- India: Opportunity and Renewal -- Japan: The West or Asia - - Singapore: Vulnerability into strength -- Thailand: Serene Networking -- Asian Characteristics -- Comparing Asian foreign Ministries -- Conclusions.
Includes bibliographical references (p. [227]-231) and index.
Keywords: Diplomatic relations; Diplomatic and consular service; Asia -- Foreign relations